Early post‐operative prediction of morbidity and mortality after a major liver resection for colorectal metastases. Issue 5 (26th October 2012) - Grąt, Michał; Hołówko, Wacław; Lewandowski, Zbigniew; Kornasiewicz, Oskar; Barski, Krzysztof; Skalski, Michał; Zieniewicz, Krzysztof; Krawczyk, Marek
Abstract Background An early prediction of poor outcomes is essential in the management of patients after a liver resection. The aim of this study was to evaluate the role of selected biochemical parameters on post‐operative day 1 (POD 1) in the prediction of morbidity and mortality after a liver resection for colorectal metastases. Method This retrospective study was based on 236 major liver resections for colorectal metastases performed between 2006 and 2011. Results of biochemical tests of blood samples obtained on POD 1 were assessed as predictors of primary outcome measures (hepatic and overall morbidity, 90‐day mortality) using multiple regression and receiver‐operating characteristics (ROC). Results Hepatic morbidity, overall morbidity and 90‐day mortality rates were 18.6%, 28.0% and 4.7%, respectively. On the basis of multiple regression analysis and comparisons of the prediction models, serum bilirubin was selected for the prediction of hepatic (>2.05 mg/dl, sensitivity 69.2%, specificity 71.2%) and overall (>2.05 mg/dl, sensitivity 61.1% and specificity 71.2%) morbidity, and aspartate aminotransferase (AST) was selected for the prediction of 90‐day mortality (>798 U/l, sensitivity 62.5% and specificity 90.4%). Discussion Biochemical analyses of blood on POD1 enables stratification of patients into low‐ and high‐risk groups for negative outcomes, with serum bilirubin associated with overall and hepatic morbidity and AST associated with mortality.